Why People Oppose Trade Institutions - On Morality, Fairness and Risky Actions - Karen Evelyn Hauge; Snorre Kverndokk; Andreas Lange (Center for Economic Studies and ifo Institute (CESifo), 2021)
We investigate how moral considerations, background conditions and risk can trigger resistance to implement trading institutions. We provide survey results on moral opposition to trade on several goods and services like body organs, sex services, surrogate mothers, trade with developing nations, and trade with carbon emissions. Complementary experimental evidence allows identifying reasons for opposing trade going beyond pure moral considerations. We relate the opposition to trade in experimental and field contexts to an aversion to imposing risks on others. We then vary both background conditions and the riskiness from engaging in actual trade in the experiment. We show that distributional concerns primarily drive opposition to trade. Providing less information about individual background conditions and distributing gains from trade more equally alleviates opposition to trade.
Keywords: C90; D63; I14; 330; trade; morality; fairness; distribution; experiment